The Urgency of Implementing Government Cooperation With Business Entities (KPBU) in the Return of State-Owned Companies : (Case Study of PDAM Tirta Meulaboh) - Kurdi, (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
This research aims to analyze the urgency of implementing Government Cooperation with Business Entities (KPBU) in an effort to make state-owned companies healthy, with a case study of PDAM Tirta Meulaboh. The main focus of this research is to explore various PPP models, such as Build-Own-Operate (BOO), Build-Operate-Transfer (BOT), Design-Build-Finance-Operate-Maintain (DBFOM), and leasing, to determine the most effective model. suitable for the revitalization of PDAM Tirta Meulaboh. The research method used is normative legal research with a conceptual approach. The research results show that the DBFOM model is the most effective option for improving PDAM Tirta Meulaboh's operations and infrastructure, because it covers the entire project cycle from design to maintenance, with ownership transfer to the government after the contract period ends. Implementing government and business entity cooperation (KPBU) is a strategic approach in handling infrastructure project financing and ensuring infrastructure needs can be met effectively. In practice, PPP refers to models such as Build-Own-Operate (BOO), Build-Operate-Transfer (BOT), Design-Build-Finance-Operate-Maintain (DBFOM), and leasing, which provide various options in managing and project funding. In conclusion, proper implementation of PPPs, especially the DBFOM model, can help governments overcome infrastructure challenges and ensure sustainable public services. Keywords: PPP, PDAM Tirta Meulaboh, Infrastructure